Human stanniocalcin: a possible hormonal regulator of mineral metabolism. - Olsen, H S (1996)
We have isolated a human cDNA clone encoding the mammalian homolog of stanniocalcin (STC), a calcium- and phosphate-regulating hormone that was first described in fishes where it functions in preventing hypercalcemia. STC has a unique amino acid sequence and, until now, has remained one of the few polypeptide hormones never described in higher vertebrates. Human STC (hSTC) was found to be 247 amino acids long and to share 73% amino acid sequence similarity with fish STC. Polyclonal antibodies to recombinant hSTC localized to a distinct cell type in the nephron tubule, suggesting kidney as a possible site of synthesis. Recombinant hSTC inhibited the gill transport of calcium when administered to fish and stimulated renal phosphate reabsorption in the rat. The evidence suggests that mammalian STC, like its piscine counterpart, is a regulator of mineral homeostasis.